Aku Bisa Memilih dan Bertanggung Jawab dengan Buku Saku Nilai Moral Anak - Ananda, Adellia Putri; Pazriah, Alimna Nur; Meilani, Vadya; Dewi, Aryanti Puspita; Agustin, Putri Ayu; Ridho, Muhammad; Hayati, Auliya Aenul (Innovative: Journal Of Social Science Research, 2025)
This study aims to develop a character education pocketbook for fourth-grade elementary school students, focusing on two core values: freedom and responsibility. The background of this research is the importance of contextual and easy-to-understand learning media to strengthen character education from an early age. The study used a Research and Development approach with a Mixed Methods approach and an Explanatory Sequential design. The study subjects included students, teachers, and parents at SDN Bima Cirebon. The results showed that the use of the pocketbook had a positive impact on students' understanding and moral attitudes. Students became more reflective, able to take responsibility for their choices, and were active in group discussions. Furthermore, teachers and parents observed behavioral changes reflecting the internalization of values, both at school and at home. The conclusions of this study indicate that the character education pocketbook is an effective, practical, and relevant learning medium for supporting character building in elementary school students, particularly in instilling the values of freedom and responsibility.